Analisis Sentimen Ulasan Game Stardew Valley pada Steam dan Google Play - Tampubolon, Surya Viari; Sulistyo, Danang Arbian (JURNAL FASILKOM, 2026)
The large number of user reviews on Steam and Google Play platforms makes manual analysis difficult and prone to subjective bias. This study aims to analyze and compare user sentiment toward Stardew Valley game reviews on both platforms using a text mining approach. The data used consist of 25,099 Steam reviews and 25,594 Google Play reviews. The text preprocessing stage includes case folding, cleansing (removal of punctuation and non-alphabetic characters), tokenization, stopword removal, and lemmatization to produce more structured data. Sentiment labeling is performed using the VADER method, followed by feature extraction using TF-IDF and classification using the Multinomial "Naïve Bayes" algorithm. Model evaluation is conducted using 5-Fold Cross Validation with accuracy, precision, recall, and F1-score as evaluation metrics. The results show that most reviews on both platforms have positive sentiment. The classification model achieves an average accuracy of 0.8151 on Steam and 0.8382 on Google Play. In addition, the model obtains an average F1-score (macro average) of 0.55 on Steam and 0.40 on Google Play. These results indicate that the model performs adequately in sentiment classification, although it still has limitations in identifying minority sentiment classes such as negative and neutral.